Given the equation:
"x^2(y-z)p + y^2(z \u2212 x)q = z^2(x-y)" The equation is a Lagrange Linear PDE and it's of the form:
"Pp+Qq=R" with:
"P=x^2(y-z); \\quad Q=y^2(z \u2212 x); \\quad R=z^2(x-y)" The auxiliary equation is in the form:
"\\frac{dx}{P}=\\frac{dy}{Q}=\\frac{dz}{R}" Thus:
"\\frac{dx}{x^2(y-z)}=\\frac{dy}{y^2(z \u2212 x)}=\\frac{dz}{z^2(x-y)}" We proceed to solve the equation.
Using the multipliers "\\frac{1}{x},\\frac{1}{y},\\frac{1}{z}"
"\\frac{\\frac{dx}{x}}{x(y-z)}=\\frac{\\frac{dy}{y}}{y(z \u2212 x)}=\\frac{\\frac{dz}{z}}{z(x-y)}\\\\" Adding up we have:
"\\frac{dx}{x}+\\frac{dy}{y}+\\frac{dz}{z}=0" Integrating through:
"\\int\\frac{dx}{x}+\\int\\frac{dy}{y}+\\int\\frac{dz}{z}=\\int0\\\\\n\\ln x + \\ln y+ \\ln z=\\ln c\\\\\n\\ln(xyz)=\\ln c\\\\\n\\bold{c_1 = xyz}"
Using the multipliers "\\frac{1}{x^2}, \\frac{1}{y^2}, \\frac{1}{z^2}" as another triplet such that the denominator vanishes:
"\\frac{\\frac{dx}{x^2}}{y-z}=\\frac{\\frac{dy}{y^2}}{z \u2212 x}=\\frac{\\frac{dz}{z^2}}{x-y}\\\\" Adding up, we get:
"\\frac{dx}{x^2}+\\frac{dy}{y^2}+\\frac{dz}{z^2}=0" Integrating through:
"\\int\\frac{dx}{x^2}+\\int\\frac{dy}{y^2}+\\int\\frac{dz}{z^2}=\\int 0\\\\\n-\\frac{1}{x}-\\frac{1}{y}-\\frac{1}{z}=c_2\\\\\n\\bold{c_2=-\\Big(\\frac{1}{x}+\\frac{1}{y}+\\frac{1}{z}\\Big)}" Therefore the solution of the PDE is:
"\\phi(c_1,c_2) = \\Big(xyz, -\\Big(\\frac{1}{x}+\\frac{1}{y}+\\frac{1}{z}\\Big)\\Big)"
Comments
Leave a comment